Melon (Cucumis melo L.) by-products: Potential food ingredients for novel functional foods? - Silva, M.A. (2021)
Background: Nowadays food wastes are a major concern. On the other hand, the demand for natural beneficial compounds to human health is increasing. Melon (Cucumis melo L.) is a very appreciated fruit, consumed all over the world, that contains large amounts of seeds and peel, which up to now are discarded. These by-products contain phytochemical compounds with great nutritional and functional potentials. Scope and approach: This review describes the scientific studies regarding nutritional, bioactive and anti-nutrients composition of melon by-products, as well as their main biological activities and industrial applications. These findings intend to contribute for future research concerning novel functional foods based on melon byproducts. Key findings and conclusions: Melon peel is a good source of minerals (potassium, sodium, magnesium, calcium) and phenolic compounds. It also contains carotenoids, namely lycopene and β-carotene. In turn, melon seeds are a good source of protein (15–36%) and fibre (7–44%). Melon seed oil is a good source of tocopherols and sterols (β-sitosterol, 0.06–289 mg/100 g oil), as well as phenolic compounds. It has an interesting fatty acid profile, very similar to soybean and sunflower oils. Moreover, melon by-products present different biological activities including antioxidant, anti-inflammatory, antidiabetic, antiulcer, antibacterial, and anti-angiogenic, fully justified by the presence of bioactive compounds. Therefore, these by-products can be considered good candidates for the development of novel functional foods, contributing to promote sustainability across food chain. Nonetheless, further research is needed, namely concerning clinical studies to fully support the development of evidencebased functional foods.